ANALISIS PEMASARAN DAN TATANIAGA ANGGUR DI BALI - -, SUHARYANTO; PARWATI, IDA AYU PUTU; RINALDI, JEMMY (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 8, No. 1 Februari 2008)
Bali grape, especially that effort at Buleleng district is one of local specific commodity that has great potency to be developed. Marketing aspect is important to support the increasing of grape farmer’s income. The number of trading institution that involved to grape marketing will influence to the length of market chain and the amount of market cost. The amount of market cost will point to the higher difference prices between producer farmer and consumer. For that purpose, analysis of marketing and trading of grape was conducted at Buleleng district. The research location was selected using purposive sampling technique at location of ‘Primatani Renovasi’ assessment at Gerokgak sub district, Buleleng. The research was done from August to December 2005 using survey method to 50 grape farmers that selected randomly and 20 grape traders that selected using snowball sampling technique. Data was analyzed descriptively to financial feasibility, market channeling, market margin, market integration, and elasticity of price transmission. The result showed that grape farming system at Gerokgak sub district had well enough prospective. It was indicated by the increasing of income per year and BCR value that has tendency to increase year by year. There was 4 grape market channeling model at Buleleng, i. e.: Model 1: farmer – commission agent – collecting trader – retailer – consumer was 14%; Model 2: farmer – collecting trader – retailer – consumer was 44%; Model 3: farmer – collecting trader – district level trader – retailer – consumer was 34%; and Model 4: farmer – retailer – consumer was 8%. The highest market margin was gained by Model 1 (3600 rps/kg), followed by Model 3 (3450 rps/kg) and Model 2 (3350 rps/kg). While, the highest share accepted by farmer was for Model 3, i. e. 37,89%, followed by Model 2 (33%) and Model 1 (31%). Market integration degree between market at farmer level and market at consumer level was low, with coefficient value was 0,199. Value of elasticity of price transmission was 0,457%. Marketing function done by grape market executor included changing function (buying and selling), physically function (transportation, distribution, and storage), facility function (grading and packing); without certification and labelling.
Keywords: Grape, Marketing, Market Margin, Market Channeling.